An acoustic study of vowel intrusion in Turkish onset clusters. Issue 1 (9th October 2018) - Bellik, Jennifer
Abstract : Studies in Articulatory Phonology (Browman & Goldstein, 1993 ) have established that what sounds like insertion of a segment can be a side effect of gestural timing relations. Based on acoustic evidence from a production experiment with six Turkish speakers, I argue that such gestural timing produces non-lexical vowels in complex onsets in Turkish—previously described as harmonizing epenthetic vowels (Clements & Sezer, 1982, inter alia). Non-lexical vowels occurred in 88.3% of tokens, and usually resembled [ɯ], failing to undergo vowel harmony. Non-lexical vowels are shorter than underlying vowels, and their F1 and F2 values are more affected by the following vowel, suggesting they are more subject to vowel-to-vowel coarticulation. These results support the hypothesis that the inserted acoustic vowels are targetless, created by timing relations between gestures, with the implication that Turkish phonology does not categorically ban complex onsets.